Multiple myeloma during pregnancy as a challenge in clinical practice - a review - Magdalena Szydełko; Joanna Szydełko; Michał Litwińczuk (Kazimierz Wielki University, 2019)
Introduction: Multiple myeloma (MM) is a hematological malignancy characterized by an abnormal proliferation and accumulation of monoclonal plasma cells. MM typically affects the elderly people with the median age at the diagnosis between 65 to 74 years. Only in < 2% of cases it is observed